COMPOSIÇÃO FÍSICO-QUÍMICA DE PÓLEN APÍCOLA DE DIFERENTES BIOMAS - FARIAS, RENATA ALMEIDA (2023)
Bee pollen is a matrix formed by floral pollen agglutinated by working bees commonly used as a food supplement due to its composition being rich in essential nutrients for the human diet and therapeutic properties. Therefore, the present study analyzed with a spectroscopical approach (ICP, FAAS, and EDXRF) the mineral content of pollens from the northeastern, southeastern, and southern regions to set a fingerprint of their constituents as a marker of their physical-chemical properties and possible geographical correlation. In addition to the scavenging activity of the samples. The pollens presented mean inhibition from 10.9 to 86.1 % with no significant difference by state, biome, or region. The ash content was between 1.77 and 4.00 %, where the pollens from Rio Grande do Norte had the highest content with statistical significance between them and those from the states of São Paulo and Paraná. Regarding color, there was a predominance of red and yellow coordinates in which the northeastern samples had a duller, darker, and less reddish profile when compared to pollens from the southeastern and southern regions. It was found X-rays peaks for the elements Br, Ca, Cu, Fe, K, Mn, P, Rb, S, Sr, and Zn in the samples with a predominance of K and Ca. The elemental distribution occurred as follows K, Ca, P, Zn, and S, in the Northeast; Mn, Rb, and Fe in the South; Cu and Sr in the Southeast. It is suggested that soil acidity was a relevant factor in the elemental distribution and regional pedogenic characteristics reflected in the composition of the studied pollens accounting for the predominance of southern samples in the Fe principal component and the abundance of K and Ca for northeastern pollens. As a result, EDXRF is a feasible technique to assess the elemental composition of pollen as a quick and environmentally friendly alternative.